Impacto de la tuberculosis pulmonar drogorresistente en la salud pública del Ecuador - Llumitaxi Tasgacho, Jessica Lizbeth (2025)
This systematic review aimed to analyse the impact of drug-resistant pulmonary tuberculosis on public health in Ecuador. The methodology followed PRISMA guidelines, conducting systematic searches in scientific databases (Pubmed, Scielo, Dialnet, Redalyc, Google Scholar and Scopus) of articles published between 2020-2024. A systematisation matrix was used to analyse 20 studies that met the inclusion criteria, assessing epidemiological, clinical and health systems aspects through a structured narrative synthesis. Methodological quality was assessed using the CASP instrument. The results showed a high prevalence of rifampicin resistance ranging from 13-88.89%, a significant TB/HIV co-infection rate of 11.3% and a worrying treatment dropout rate of 39.6%, almost three times the global average. Only 50% of resistance-associated mutations were identified as being included in the WHO catalogue, showing unique patterns of genetic resistance in the country. Socio-economic factors, especially in rural and border areas, were found to have a greater influence on disease dynamics than migration patterns. The research also revealed the presence of 15 MDR, 4 pre-XDR and 2 XDR strains, along with a worrying increase in resistance to fluoroquinolones. It is concluded that drug-resistant TB represents a complex and multidimensional challenge for Ecuadorian public health, requiring a comprehensive strategy that addresses social determinants, optimises treatment regimens, improves access to early diagnosis and strengthens epidemiological surveillance to effectively control this health threat